Association between university students’ personality traits and smoking habits - Yazıcı, Hikmet; Reisoğlu, Serpil; Kahveci, Harun (Journal of Dependence, 2010)
Objective: The aim of this study was to investigate the association between university students’ personality traits and their smoking habits. Methods: As a descriptive cross-sectional study, the study was performed with 421 students aged 17-30 (Mean = 21.64, SD = 2.59) studying at the Karadeniz Technical University. Personality traits were evaluated by the Eysenck Personality Questionnaire Revised-Abbreviated Form (EPQR-A). Logistic regression analysis was used to examine whether students’ personality was associated with their smoking habits. Results: Neuroticism and psychoticism were the most significant predictors of smoking. There was not any significant relationship between extraversion and smoking. Other predictors such as age, gender, grade level and parental smoking could contribute to the maintenance of smoking habits. Males were more likely than females to be current smokers, and increasing age increased the likelihood of being a current smoker. Conclusion: These results show that both higher levels of neuroticism and higher levels of psychoticism are independently associated with smoking habits.